The growth of e-marketing in business-to-business industry and its effect on the performance of businesses in Pakistan: marketing success - Sheikh, Adnan Ahmed; Shahzad, Arfan; Ku Ishaq, Awanis (Hipatia Press, 2017)
E-marketing has emerged as one of the significant drivers in sustaining the firms competitive advantage. So far, there is a lack of systematic empirical evidence regarding the marketing activities which are drastically affected by the use of e-marketing in small and large firms of Pakistan and their consequent performance outcomes. However, the objective of this study is to examine the technological, organizational and environmental factors on the performance of small and large firms in Pakistan with mediating role of E-Marketing uses and its generlizibality on countries with similar economic situation. Cross sectional data were collected from 257 manufacturing companies in Pakistan; general manager marketing were selected as the data collection sources. Additionally, SmartPLS 3.0, two step path-modeling has been used to examine the direct as well as indirect hypothesis of the current study. However, the results generated from SmartPLS (SEM) path-modeling found that, with regard to direct relationships, three variables (technology orientation, top management support, use of e-marketing) out of five including mediation variable have found significant positively associated with firm performance, however, only one (competitive pressure) has found negatively significant with firm performance. Finally, in terms of use of e-marketing as mediating variable between the relationships of technological, organizational, environmental factors and firm performance, three out of four (independent variables) indicate partial mediation including technological factors (technology orientation), organizational factors (top management support) and environmental factors (competitive pressure). However, market orientation had shown insignificant results both in the direct relationship as well as by including E-Marketing uses.